2018
DOI: 10.1017/s1431927618000144
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Human Retinal Pigment Epithelial (hRPE) Sheets: A Search for Suitable Storage Conditions

Abstract: The advancement of human retinal pigment epithelial cell (hRPE) replacement therapy is partly dependent on optimization of cell culture, cell preservation, and storage medium. This study was undertaken to search for a suitable storage temperature and storage medium for hRPE. hRPE monolayer sheets were cultured under standard conditions at 37°C and then randomized for storage at six temperatures (4, 16, 20, 24, 28, and 37°C) for 7 days. After revealing a suitable storage temperature, hRPE sheets were subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In a previous study on preservation of cultured primary human fetal RPE, we showed that the fraction of pigmented cells was inversely related to storage temperature [ 7 ]. The precise mechanisms behind these results were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study on preservation of cultured primary human fetal RPE, we showed that the fraction of pigmented cells was inversely related to storage temperature [ 7 ]. The precise mechanisms behind these results were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure length and gain were maintained at a constant level for all samples and the fluorescence intensities of the FITC or Cy3 fluorochromes, which were conjugated to the secondary antibodies, were within the dynamic range of the camera. Immunofluorescence per cell was quantified by custom-made macros for ImageJ, as described previously [ 7 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After washing the cultures three times with PBS, photomicrographs were captured at 200x magnification and subsequently analyzed using custom-made macros with ImageJ (National Institutes of Health, Bethesda, MD), as described previously. 6…”
Section: Live/dead Viability Assaymentioning
confidence: 99%